La sátira política y de las costumbres del periódico El Bateo : Medellín 1907-1957 (2010)
ABSTRACT: This article is about the satirical newspaper El Bateo, which was published in Medellín between 1907 and 1957; here it is provided a description of its speech and a brief analysis of its political satire and customs. This newspaper acquires importance not only as a valuable resource, and little exploited, for the social and political history study of Medellin, but as a cultural product that is worthful to be analyzed in its context. In addition, El Bateo becomes a new kind of satirical press, different in19th century, because it undermines the exclusive right to politics, for entering into the customs satire and humorous trite remarks. Furthermore, the extensive publication of caricatures gave the newspaper the possibility of reaching a wide public, even illiterate.